The struggle for autonomy - Abd Razak, Dzulkifli (2010)
THE struggle for any form of liberties, including that of academic freedom, is similar to that of challenging the status quo. In the case of academic freedom, it is about changing the rules of the game that have long curtailed the spirit of intellectuals ranging from dampening it through to a number of bureaucratic processes, legal or otherwise. The more tedious the process, the more intense the struggle. Still, autonomy is essential for universities and higher education to surge forward.